Msc. Entrepreneurship and Innovation Management Business Plan - Pabrekar, Ketki Prasad (2016)
Pink Mud is an online brand of perfumes and fragrance mists, sold across six major e-commerce portals. Pink Mud aims to produces high quality fine French fragrances for younger women. In the second year itself we have a strong product line of 14 fragrances in the form of body mists, perfumes and pocket perfumes